Abstract of Invited Speaker : An Overview of Ganoderma lingzhi Constituents on α-Glucosidase and Aldose Reductase Inhibitory Activity - Sri Fatmawati (IPTEK Journal of Proceedings Series, 2015)
Ganoderma lingzhi is the medicinal woody mushroom which have been known to have hundreds bioactive compounds. The lanostane-type triterpenoids with carboxyl group in the side chain or known as ganoderma acids were isolated from the fruiting body of G. lingzhi. Some of these compounds were established as active inhibitors of α- glucosidase and human recombinant aldose reductase in vitro. The research objective is to enlighten the role of structural requirement of ganoderma acids both for α-glucosidase and aldose reductase inhibition. Comparing the inhibitory activity of these two enzymes, the structure–activity studies of ganoderma acids showed that the hydroxyl substituent at C-11 and the carboxylic group in the side chain are an important feature both for the recognition of α-glucosidase and human recombinant aldose reductase inhibitory activity. Furthermore, the double- bond moiety at C-20 and C-22 in the side chain and the hydroxyl substituent at C-3 of ganoderma acids enlarge the inhibitory activity of both enzymes. These outcomes offer an approach which to regard as the structural requirements of lanostane type triterpenoids acids from G. lingzhi. A consideration of these requirements is essential in order to develop a new type for substances that can be improved to prevent the diabetic complications